2014
DOI: 10.2147/rrcc.s56112
|View full text |Cite
|
Sign up to set email alerts
|

Multielectrode phased radiofrequency ablation compared with point-by-point ablation for pulmonary vein isolation – outcomes in 539 patients

Abstract: Purpose: To provide data on acute and long-term outcomes from pulmonary vein isolation with the pulmonary vein ablation catheter (PVAC) in patients with paroxysmal or persistent atrial fibrillation (AF). Methods:This was a single-center, retrospective, nonrandomized, case control study. Patients with documented symptomatic paroxysmal or persistent AF were treated with PVAC or with pointby-point radiofrequency ablation guided by the NavX™ mapping system. All follow-up visits were conducted in our center at 1 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Recently, the multipolar RF ablation technology has recently been clinically investigated for treating AF. Spitzer et al conducted several clinical studies in which they compared the success rate and effectiveness of point-to-point ablation and multipolar phase RF ablation in 539 patients [5]. Basu et al reported that the bipolar ablation for AF was substantially shorter of procedure time and a greater guarantee of transmural lesions compared with the unipolar ablation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the multipolar RF ablation technology has recently been clinically investigated for treating AF. Spitzer et al conducted several clinical studies in which they compared the success rate and effectiveness of point-to-point ablation and multipolar phase RF ablation in 539 patients [5]. Basu et al reported that the bipolar ablation for AF was substantially shorter of procedure time and a greater guarantee of transmural lesions compared with the unipolar ablation [6].…”
Section: Introductionmentioning
confidence: 99%
“…The phase-shift angle RF ablation technique has recently been clinically investigated for treating AF, and the first related clinical result for PVI was published by Wieczorek et al [1]; they reported that the phase-shift angle RF energy used in the PVI procedure was safer and that the procedure was substantially shorter compared with the conventional procedure [2]. Spitzer et al [3] conducted several clinical studies in which they compared the success rate and effectiveness of point-to-point ablation and multi-electrode phase RF ablation in 539 patients. Bulava et al [4] performed a rando-mised comparison between phase-shift angle RF ablation and point-to-point ablation for AF and reported similar clinical success rates for both procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91] There is some, though limited, data available on the achievement of improved procedural success rates using multielectrode ablation in comparison with using single-electrode irrigated ablation. 92,93 Importantly, despite the early mixed success rates for these emerging technologies, these studies typically represented first-or early-generation devices that had likely not reached full maturity or efficacy. The goal of performing longer or larger contiguous lesions with a single ablation procedure remains attractive, especially for its potential to improve procedural efficiency.…”
Section: Efforts To Address Factors Affecting Lesion Formationmentioning
confidence: 99%